(untitled) (Bioagro, 2022)
Anther culture is a tool that allows the production of homozygous double haploid plants, and is a proper and viable alternative for crop improvement. However, the success of its application depends on a number of factors that affect its efficiency. Thus, the objective of this study was to determine the microspore stages associated with flower bud development, as well as to evaluate sterilization methods and development of Physalis peruviana anthers in four culture media. The late uninucleate stage, suitable for initiating androgenesis, was found in flower buds between 7.85 and 9.37 mm polar length. The lowest levels of oxidation (10 %) and contamination (20 %), and the highest anther viability (70 %) were recorded under surface sterilization treatment with ethanol (70 %) for 3 min and NaClO (2 %) for 15 min. Callus formation and green plant regeneration were obtained on B5 and LS media, indicating their usefulness in breeding programs.